The Effect Of Service Quality And Price Perception On Customer Satisfaction Of Gojek Applications In Surabaya - Wijaya, Amanda Okky; Aminah, Siti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
As the growth and development of the Indonesian state is getting higher, problems arise that require solutions that can facilitate and accelerate movement from one place to another quickly despite the long distance traveled. Service quality and price perceptions are very important to maintain, increase customer satisfaction and the increasing quality of service provided will increase customer satisfaction with the Gojek application in Surabaya. The price match with the benefits obtained makes customers will make the Gojek application their first choice. This study aims to analyze the effect of service quality and price perceptions on customer satisfaction of the Gojek application in Surabaya. This study uses quantitative methods with the sampling technique used, namely Probability Sampling. A sampling technique that does not provide equal opportunities or opportunities for each element or member of the population to be selected as a sample with a Purposive Sampling approach. The sample of this study amounted to 70 respondents who are customers or have made transactions more than once in the Gojek application and live in Surabaya. The technique used for data collection uses primary data obtained through questionnaires distributed to respondents. The analysis technique used in this study uses smartPLS through validity tests, reliability tests, hepotisis tests. Based on the research, it can be concluded that service quality has a positive and significant effect on customer satisfaction. Likewise, the price perception variable has a positive and significant effect on customer satisfaction for the Gojek application in Surabaya.